Simultaneous incorporation of magnesium and carbonate in apatite: effect on physico-chemical properties - Marcia S. Sader; Kanthi Lewis; Gloria A. Soares; Racquel Z. LeGeros (Materials Research, 2013)
Synthetic apatites are widely used both in the dental and the orthopaedic fields due to their similarity in composition with the inorganic phase of hard tissues. Biologic apatites are not pure hydroxyapatite (HA), but are calcium-deficient apatites with magnesium and carbonate as minor but important substituents. The aim of the present study was to produce a more soluble biomaterial through the simultaneous substitution of magnesium and carbonate in the apatite structure to accelerate the degradation time in the body. The physico-chemical and dissolution properties of unsintered magnesium and carbonate-substituted apatite (MCAp) with similar Mg/Ca molar ratio (0.03) and varying C/P molar ratio were evaluated. The resultant powders were characterised using several techniques, such as FTIR, TGA, XRD, ICP and SEM, while the release of calcium ions in a pH 6 solution was monitored using a Ca-ion selective electrode. The results showed a decrease of crystallite size and an increase in the release of calcium to the medium as the carbonate content in the samples increased.